A class of non-analytic functions for the global solvability of Kirchhoff equation. (April 2015) - Hirosawa, Fumihiko
Abstract: We consider the global solvability to the Cauchy problem of Kirchhoff equation with generalized classes of Manfrin's class. Manfrin's class is a subclass of Sobolev space, but we shall extend this class as a subclass of the ultradifferentiable class, and we succeed to prove the global solvability of Kirchhoff equation with large data in wider classes from the previous works.